Posttreatment Recurrence and Death Patterns in Patients with Advanced Esophageal Cancer. (9th July 2022) - Zhang, Xiangmei; Wang, Hui; He, Dongwei; He, Ming; Chen, Xin; Zhao, Jidong
Abstract : Objective . To investigate into the clinical factors associated with posttreatment recurrence and death patterns in patients with advanced esophageal cancer. Methods . Clinical information of patients with recurrence/metastasis and death after radical resection of esophageal cancer at our hospital between January 1, 2005, and December 31, 2015, were retrospectively collected and followed up. Postoperative recurrence-free survival time, postrelapse survival time, and overall survival time were compared among the metabolic-associated, organ failure-associated, and anastomotic recurrence-associated mortality groups. Results . Five hundred and ninety-five qualified patients were retrieved, including 456 males and 139 females, with an average age of 58 ± 7.56 years. There were 57 cases of TNM-1 stage, 131 cases of TNM-2 stage, 365 cases of TNM-3 stage, and 42 cases of TNM-4 stage. There were 547 cases of squamous cell cancer and 48 cases of nonsquamous cell cancer. There were significant differences in age (p < 0.01 ), tumor location (p < 0.01 ), and lymph node metastasis (p = 0.04 ), recurrence type (p < 0.01 ) by one-way ANOVA, and recurrence-free survival (p = 0.02 ) and postrecurrence survival (p < 0.01 ) by Kaplan-Meier survival curve analysis among the three main death causes. Conclusions . Age, tumor location, and lymph node metastasis were significantly different among metabolic-associated, organ failure-associated, and anastomotic recurrence-associated mortality of recurrent EC patients.